Penguatan Literasi Membaca Melalui Pojok Baca: Program Pengabdian di Desa Cempaka Barat - Alna Listia; Ades Ades; Adil Pratomo; Aditya Marwan; Afdhol Dinil Haq; Al Tiyas Fitriani; Alin Dwi Putri; Amanda Defina; Amelia Ramadani; Anggraini Fitri Wulandari; Nurul Afifah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The reading corner program is one of the literacy strengthening strategies that is simple yet effective in encouraging elementary school students’ reading interest. The main problem underlying this activity is the low reading interest of elementary school students, who tend to spend more time playing than reading books. This condition affects the suboptimal development of a reading culture and students’ learning outcomes. The strength of the reading corner lies in its accessibility, flexibility in arrangement, and its ability to create a conducive, enjoyable learning atmosphere that is close to students’ daily lives. This community service aims to increase reading interest as well as to build a literacy culture at SD Negeri 2 Cempaka. The method used is Participatory Action Research (PAR), which includes planning, action implementation, observation, and evaluation to obtain comprehensive field data. The results show that the presence of the reading corner provides an alternative space for students to read before lessons or during breaks. Teachers are actively involved in guiding students, such as giving simple directions or asking them to retell the content of their reading. Students who initially preferred playing gradually became accustomed to reading independently. Other impacts observed include increased teacher involvement, the growth of book collections, and the establishment of a classroom environment that supports the School Literacy Movement (SLM). Thus, it can be concluded that the implementation of the reading corner program through the PAR approach has proven effective in fostering reading interest, strengthening literacy culture, and making a positive contribution to improving the learning quality of elementary school students.